2010
DOI: 10.1007/s10571-010-9571-3
|View full text |Cite
|
Sign up to set email alerts
|

Chromaffin Progenitor Cells from the Adrenal Medulla

Abstract: Chromaffin cells of the adrenal medulla are neural crest-derived cells of the sympathoadrenal lineage. Different lines of evidence suggest the existence of a subpopulation of proliferation-competent progenitor cells even in the adult state. The identification of sympathoadrenal progenitors in the adrenal would greatly enhance the understanding of adrenal physiology and their potential role in adrenal pathogenesis. Isolation and differentiation of these progenitor cells in culture would provide a tool to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…Furthermore, it is also unclear, which types of progenitors or stem cells that persist and are maintained in the postnatal adrenal. It has been suggested that a subpopulation of proliferation competent progenitor cells continues to exist in the adult adrenal medulla Ehrhart-Bornstein et al, 2010). In addition to the adaptation to physiological needs, these progenitor cells may be involved in the development of stress-related hyper activation and hyperplasia of the adrenal and potentially in tumor development (Molatore et al, 2010;Powers et al, 2007).…”
Section: Chromaffin Progenitor Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it is also unclear, which types of progenitors or stem cells that persist and are maintained in the postnatal adrenal. It has been suggested that a subpopulation of proliferation competent progenitor cells continues to exist in the adult adrenal medulla Ehrhart-Bornstein et al, 2010). In addition to the adaptation to physiological needs, these progenitor cells may be involved in the development of stress-related hyper activation and hyperplasia of the adrenal and potentially in tumor development (Molatore et al, 2010;Powers et al, 2007).…”
Section: Chromaffin Progenitor Cellsmentioning
confidence: 99%
“…We have for the first time been able to prove the existence of proliferation and differentiation-competent sympathoadrenal progenitor cells within the adult adrenal medulla and have established methods for their isolation from bovine (Chung et al, 2009;Ehrhart-Bornstein et al, 2010;Masjkur et al, 2014) and human (Santana et al, 2012) adrenals. Under low-attachment cell culture conditions, where adherence to the culture dish is prevented, these cells express progenitor markers, have in vitro self-renewing capacity and grow in spheres, which we called chromospheres.…”
Section: Chromaffin Progenitor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative method to replenish DA in PD, chromaffin cells grafts have been proposed due to their ability to synthesize and release catecholamines. Nevertheless, the majority of chromaffin cells in the adult adrenal medulla produce epinephrine while only 1% of the population produces dopamine (Ehrhart-Bornstein et al, 2010).…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…This protocol significantly increased the Table 2 Trials of adrenal chromaffin cell grafts in PD patients. number of TH positive dopaminergic neurons and dopamine secretion, while norepinephrine and epinephrine production was reduced (Chung et al, 2009;Ehrhart-Bornstein et al, 2010;Vukicevic et al, 2012). Currently, our laboratory is assessing the viability of chromosphere grafts and its effects on behavior.…”
Section: Chromaffin Cell Transplants In Animal Pd Modelsmentioning
confidence: 99%